2018
DOI: 10.1111/faf.12304
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics and noise in fisheries recruitment: A global meta‐analysis

Abstract: The relative importance of environmental and intrinsic controls on recruitment in fishes has been studied for over a century. Despite this, we are not much closer to predicting recruitment. Rather, recent analyses suggest that recruitment is virtually independent of stock size and, instead, seems to occur in distinct environmental regimes. This issue of whether or not recruitment and subsequent production are coupled to stock size is highly relevant to management. Here, we apply empirical dynamical modelling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 68 publications
2
50
0
Order By: Relevance
“…This means that the processes from hatching to recruitment are more stochastic by environmental variability than currently recognized. Accordingly, we support the conclusion of recent meta‐analyses to emphasize the emerging need for understanding the environmental effects on survival and recruitment processes of fish (Cury et al., ; Munch et al., ; Szuwalski et al., ). Furthermore, the approaches in studies on recruitment mechanisms should also be reconsidered.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This means that the processes from hatching to recruitment are more stochastic by environmental variability than currently recognized. Accordingly, we support the conclusion of recent meta‐analyses to emphasize the emerging need for understanding the environmental effects on survival and recruitment processes of fish (Cury et al., ; Munch et al., ; Szuwalski et al., ). Furthermore, the approaches in studies on recruitment mechanisms should also be reconsidered.…”
Section: Discussionsupporting
confidence: 88%
“…Another controversial issue is the relative roles of density-dependent (self-regulating) and density-independent (environmentally regulating) processes throughout the life stages (Andersen et al, 2017;Minto et al, 2008;Myers & Barrowman, 1996;Pierre, Rouyer, Bonhommeau, & Fromentin, 2018). Recent meta-analyses showed that the spawner-recruitment relationships were weaker than previously recognized (Cury et al, 2014;Munch, Giron-Nava, & Sugihara, 2018;Szuwalski et al, 2015). For sardine, the strong density dependence was found at the time of spawning.…”
Section: Discussionmentioning
confidence: 99%
“…As in asymptotic spawner–recruitment models, it has been considered that density‐dependent effects dominate the regulation of populations, even though the SSB–R relationships are highly variable (Andersen et al, ; Minto et al, ; Myers & Barrowman, ). On the contrary, recent meta‐analyses showed that the SSB–R relationships were weaker than previously recognized, highlighting the need to evaluate the effects of density‐independent climate impacts on recruitment more intensively (Cury et al, ; Munch et al, ; Szuwalski et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…The relative roles of density‐dependent and density‐independent processes throughout the life history are of considerable significance in the population dynamics of fish (Andersen, Jacobsen, Jansen, & Beyer, ; Archambault, Pape, Bousquet, & Rivot, ; Cowan et al, ; Houde, , ; Myers, ; Nash, 1998; Nash, & Dickey‐Collas, ). Indeed, a controversial issue has been the relative dominance of density‐dependent (Andersen et al, ; Minto et al, ; Myers & Barrowman, ) versus density‐independent effects (Cury et al, ; Munch, Giron‐Nava, & Sugihara, ; Szuwalski et al, ) in SSB–R relationships. Furthermore, the relative roles may change over the life history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation